Uses of Braces and Orthotics for Conservative Management of Foot and Ankle Disorders. Issue 3 (3rd August 2018) - Elattar, Osama; Smith, Tyler; Ferguson, Adam; Farber, Daniel; Wapner, Keith
Nonsurgical management is almost always considered the first-line treatment for the vast majority of foot and ankle pathologies. Foot orthoses, shoe modifications, and therapeutic footwear are considered essential tools for successful conservative management of different foot and ankle disorders. Orthopedic foot and ankle surgeons should have a meticulous understanding of the lower extremity biomechanics as well as the pathoanatomy and the sequelae of diseases affecting the foot and/or ankle. This is essential to the understanding of the desired effects of the different inserts, orthotics, shoe modifications, or braces that may be prescribed for these conditions. In this article, we will summarize the orthoses used for treatment of the most commonly encountered foot and ankle pathologies, with the exclusion of treatment for the diabetic foot because of the unique requirements of that disease process.